"Science" and Literary Soundscapes, Neuroscience and Oral History: Research Notes from Iranian Studies. (14th January 2016) - Amin, Camron Michael
Abstract : We have no shortage of texts to recover representations of sound. There is also an underutilized, renewable—yet, if not recorded, ephemeral—source that can help us recover the sounds of the vanishing past: oral history. The discovery of soundways and historically contextualized soundscapes is a compelling project on its own. By "soundways, " I mean the "paths, trajectories, transformations, mediations, practices, and techniques—in short, the way—that people employ to interpret and express their attitudes or beliefs about sound." Global culture can be thought of as flowing through technoscapes, ethnoscapes, mediascapes, financescapes, and ideascapes, Arjun Appadurai has argued. The flow of global culture through these "scapes" would be represented in local soundscapes. Oral history interviews are one way to follow the flow to the level of the individual. And while sensory memories—especially echoic, haptic, and iconic—are being investigated in the context of medical and psychological research, they are not often considered in connection with social history.